Essays on inflation and indexation - Giersch, Herbert; Friedman, Milton; Fellner, William; Bernstein, Edward M.; Kafka, Alexandre (Washington : American Enterprise Institute for Public Policy Research, 1974)
This book present five views on whether a general system of escalator clauses sometimes called indexation or monetary correction would be a useful addition to the U.S arsenal of anti-inflationary weapons.
Includes bibliographical references.
usc 14/05/18
Loans
Keywords: Inflation (Finance); Indexation (Economics)